2007
DOI: 10.1111/j.1572-0241.2007.01223.x
|View full text |Cite
|
Sign up to set email alerts
|

Are Chronic Hepatitis C Viral Infections More Benign in Patients With Hemophilia?

Abstract: HCV infections in hemophiliacs may be less severe than in HCV infected patients without hemophilia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…Finally, in a recent study, Assy et al 30 have shown that chronic HCV infection in 12 patients with haemophilia causes less severe liver disease than in patients without haemophilia, and that the extent of histological abnormalities correlates with the severity of the underlying coagulopathy.…”
Section: Prothrombotic Factors and Hcv-associated Hepatic Fibrosis: Hmentioning
confidence: 95%
“…Finally, in a recent study, Assy et al 30 have shown that chronic HCV infection in 12 patients with haemophilia causes less severe liver disease than in patients without haemophilia, and that the extent of histological abnormalities correlates with the severity of the underlying coagulopathy.…”
Section: Prothrombotic Factors and Hcv-associated Hepatic Fibrosis: Hmentioning
confidence: 95%
“…56,58,59 In addition, patients with factor V Leiden appear to have a faster progression of hepatitis, 60 whereas hepatitis C-related liver disease in patients with hemophilia has been suggested to be milder compared with hepatitis C progression in patients without hemophilia. 61 The concept of rebalanced hemostasis-laboratory evidence From the preceding 2 sections, it is evident that patients with liver disease may experience both bleeding complications as well as thrombotic episodes. The occurrence of bleeding complications has been explained by the reduced platelet count, the decreased plasma levels of coagulation factors, and the decreased plasma levels of inhibitors of fibrinolysis.…”
Section: Clinical Evidence Of Hypercoagulationmentioning
confidence: 99%
“…Observational studies in humans have suggested a faster disease progression of patients with fibrosis who were also carriers of factor V Leiden, although not all studies agree . In addition, patients with hemophilia and hepatitis‐related fibrosis appeared to have a slower disease progression compared to patients with hepatitis without hemophilia . The combined results of experimental animal studies and observational human studies have led to the proposal that anticoagulant drugs may be used as adjunct therapy in patients with early cirrhosis to prevent disease progression, decompensation, and delay or prevent liver transplantation or death .…”
Section: Intrahepatic Thrombosis As a Contributor To Disease Progressionmentioning
confidence: 99%
“…109,110 In addition, patients with hemophilia and hepatitis-related fibrosis appeared to have a slower disease progression compared to patients with hepatitis without hemophilia. 111 The combined results of experimental animal studies and observational human studies have led to the proposal that anticoagulant drugs may be used as adjunct therapy in patients with early cirrhosis to prevent disease progression, decompensation, and delay or prevent liver transplantation or death. 112 Indeed, a recent randomized clinical study showed that prolonged daily administration of low-molecular-weight heparin substantially delayed decompensation and death, without significant side effects.…”
Section: Intrahepatic Thrombosis As a Contributor To Disease Progrementioning
confidence: 99%